Surgical Management of the Spinal Cord Vascular Lesions Supplied by the Anterior Spinal Artery. Issue 1 (April 2016) - Neckrysh, Sergey; Krotenkov, Pavel
Introduction: Surgical management of the spinal cord (SC) vascular malformations supplied by the anterior spinal artery (ASA) is still disputable and technically demanding. Treatment options include endovascular, open surgical, or a combination of the two methods. All options have a risk of SC ischemia resulting from retraction or dissection through the SC, coagulation or embolization of the SC supplying artery. The authors consider surgery to be an ultimate solution for this pathology. We present four patients with symptomatic anteriorly placed vascular malformations in which total excision of the lesions was performed by a posterolateral approach with unilateral arthropediculectomy. Materials and Methods: The case series included 4 patients (2 male, 2 female), ages 23–56 (mean 32). All patients initially presented with weakness in the lower limbs and (or) pelvic organ dysfunction. The preoperative evaluation consisted of a neurologic/urodynamic evaluation, and imaging studies. In all patients the neuroimaging included magnetic resonance imaging (MRI) and selective spinal angiography (SSA), confirming the diagnosis of arteriovenous malformation in two patients, spinal hemangioma in one, and cavernous angioma in another. Vascular malformations were supplied by the ASA in 2 cases and by both the anterior and posterior spinal arteries in the other two cases. Neurologic status was based on duration of symptoms, the presence of motor, sensory or sphincter dysfunction and grading by the Frankel scale. Two patients with malformations supplied by anterior and posterior spinal arteries underwent endovascular intervention to reduce the intensity of blood flow by means of embolization. In all patients the surgery was three stage procedure made in one operative session: 1. Posterolateral approach with unilateral arthropediculectomy; 2. Microsurgical resection of the malformation; 3. Posterior instrumented fusion (to avoid postlaminectomy kyphosis). The patients were positioned prone on the Jackson table with 3-point Mayfield clamp affixed to the head placed in a neutral position, to allow adequate posterior fusion. Posterolateral approach with unilateral arthropediculectomy allowed to obtain adequate visualization of the anterior and lateral aspects of the SC for direct manipulations on the malformation and its feeding vessels, while avoiding direct manipulations on the SC or its dissection. Cervical/thoracic posterior screw fixation and fusion was performed using freehand technique considering unique osteoligamentous and vascular anatomy. None of the screws were malpositioned or interfered with post-op SSA. Results: Postoperative SSA demonstrated complete disappearance of the malformation in all cases. Neurological outcome improved in all patients. Follow-up Frankel grades showed improvement to grade E in 2 patients (50%), and reached grade D in 2 (50%). Conclusion: Despite the increasing use of endovascular techniques there is a significant role for operative management of spinal cord (SC) vascular malformations having complicated/combined arterial feeding. Treatment should be individualized and integrated by endovascular and surgical procedures, considering lesional angioarchitecture and clinical status of the patient. Surgical approach should provide the exposure of the anterior and lateral aspects of the SC for direct manipulations on the malformation and its feeding vessels, and exclude manipulations and dissection of the SC.